PENGARUH LATIHAN WALL DRILLS TERHADAP KECEPATAN LARI PADA TIM FUTSAL PUTRA SMK SWASTA YAPIM MANDAU - Santoso, Wilman; Zainur, Zainur; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that there still a shortage in the men's futsal team of Yapim Mandau Private Vocational School, when they dribble they cannot pass the opposing players because they do not have the speed to run dribbling away from the opponent or when going to grab the ball from the opponent. The purpose of this research was to determine the effect of Wall Drills training on running speed on the men's futsal team at Yapim Mandau Vocational School. The place of this research was carried out in the field of the Private Vocational School inapim Mandau. The research was carried out on 27 July 2019 to August 5, 2019. The samples used in this research were 10 male futsal players of the Private Vocational School Yapim Mandau. Because the research uses one group, this research uses a one-group pretest-post test design approach. In this design there is a pretest before being given treatment. Based on the analysis of pree-test and post-test data there was an increase of 0.5 seconds and based on statistical analysis of inference using the t-test yielded a tcount of 5.03 which was greater than the table of 1,812. Means tcount> ttable. So it can be concluded that the Wall Drills training that has been given has a positive impact on running speed. Based on the results of the analysis, it was concluded that there was an effect of the Wall Drills training on running. Key Words: Wall Drill Training, Running Speed